Is there philosophy in the Hebrew Bible? Some recent affirmative perspectives - Gericke, Jaco (Journal for semitics, 2014)
This article discusses a selection of the most recent examples from both biblical scholarship and Jewish philosophy of the construction of the Hebrew Bible as a philosophical resource. By way of a descriptive overview of the relevant ideas in the writings of exemplars such as Davies, Hazony, Gericke, Glouberman and Sekine, the study reveals a neglected albeit radical trend in the contemporary attempted return of philosophy to Hebrew Bible interpretation and vice-versa. These new developments are labelled "philosophical maximalism", involving as they do the classification of the entire corpus of the Hebrew Bible as philosophical literature, in one sense or another.